2023
DOI: 10.3390/polym15102301
|View full text |Cite
|
Sign up to set email alerts
|

Isotherm and Kinetic Study of Metal Ions Sorption on Mustard Waste Biomass Functionalized with Polymeric Thiocarbamate

Abstract: The presence of high concentrations of metal ions in effluents resulting from industrial metal coatings is a well-known fact. Most of the time, such metal ions, once they reach the environment, significantly contribute to its degradation. Therefore, it is essential that the concentration of metal ions is reduced (as much as possible) before such effluents are discharged into the environment to minimize the negative impact on the quality of the ecosystems. Among all methods that can be used to reduce the concen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…These include a fast adsorption rate, 20 ease of handling operation, 21 and high adsorption capacity with higher metal selectivity. 22,23 This article is licensed under CC-BY-NC-ND 4 Pyrazole compounds are preferred as mono-or bidentate ligands because they can align with heavy metals through two centers and two adjacent N atoms. 24−26 It was found that this type of molecule can form powerful adsorbents with intriguing qualities, including high selectivity absorption, stability, chemical derivatization, eco-friendliness, biodegradability, and harmlessness to living beings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include a fast adsorption rate, 20 ease of handling operation, 21 and high adsorption capacity with higher metal selectivity. 22,23 This article is licensed under CC-BY-NC-ND 4 Pyrazole compounds are preferred as mono-or bidentate ligands because they can align with heavy metals through two centers and two adjacent N atoms. 24−26 It was found that this type of molecule can form powerful adsorbents with intriguing qualities, including high selectivity absorption, stability, chemical derivatization, eco-friendliness, biodegradability, and harmlessness to living beings.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, polymer adsorbent structure-design ability with highly rich functional group content of −OH, −NH 2 , and −COOH makes for many desirable characteristics when treating wastewater. These include a fast adsorption rate, ease of handling operation, and high adsorption capacity with higher metal selectivity. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the adsorbents play a significant role during the adsorption process. In recent years, in order to improve the adsorption properties of un-artificial cellulose for heavy metal ions removal, vast research efforts have been made to introduce adsorption groups with high selectivity to functionalize the original cellulose through a series modification methods such as acidification, etherification, grafting polymerization, cross-linking, and esterification [ 2 , 16 , 20 , 21 , 22 , 23 ]. Among these reported functionalization strategies, PPy has been widely investigated for enhancing its adsorption capacity towards heavy metal ions owing to its merits of inexpensiveness, ease of polymerization, and environment durability [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Du and co-workers prepared PPy/MLS nano composites with a maximum adsorption capacity of 343.64 mg g –1 at 25 °C for removing Cr(VI) [ 27 ]. Chen prepared the PPy modified corn using the FeCl 3 oxidation approach, and the obtained adsorbent of PPy/corn exhibited a saturated adsorption capacity of 84.7 mg g –1 for Cr(VI) [ 21 ]. Maity et al reported a PPy composite containing a thiol-functionalized chelating group for the removal of Hg(II), with a maximum adsorption capacity of 1736.8 mg g –1 at 25 °C [ 28 ].…”
Section: Introductionmentioning
confidence: 99%